Intercultural Education Values: Insights from Primary School Teachers’ Views in North Macedonia - Adili, Bujar; Ameti, Makfirete; Rushidi-Rexhepi, Jehona; Zenki-Dalipi, Arbresha; Agai, Arita (Journal of Research in Education and Pedagogy, 2025)
In an increasingly diverse educational landscape, understanding how teachers perceive the foundational values of intercultural education is critical for fostering inclusive classrooms and promoting social cohesion. This research investigated whether variables such as gender, level of education, prior intercultural education, teaching experience, and the school cultural structure affect teachers’ views on the values promoted by intercultural education. To explore these relationships, a structured questionnaire was designed and pilot‑tested before full deployment, ensuring clarity and relevance of all items. A 5-point Likert Scale consisting of 8 items was applied to 217 primary school teachers in the Republic of North Macedonia. The Scale’s reliability (Cronbach’s Alpha) coefficient was found to be 0.91. Data collection achieved a 72% response rate, allowing for robust subgroup comparisons across gender, educational attainment, and other factors. T-tests and Scheffé tests were performed to determine whether there are statistically significant differences in teachers’ perceptions based on the investigated variables. Significant differences were observed based on gender, teaching experience, the cultural structure of the school, and prior intercultural education. Detailed post‑hoc analyses clarified which groups differed most markedly, highlighting the impact of targeted training. Teachers believe that intercultural education, above all, promotes “tolerance towards the culturally different”, “reduction of stereotypes and prejudices”, and “coexistence of different cultures”. Drawing on these findings, practical recommendations are offered for policymakers and school leaders. Teachers need permanent training on cultural diversity to sustain and deepen their intercultural competence and to translate these values into everyday classroom practice.